Recent controversies in liver transplantation (Journal of Patan Academy of Health Sciences, 2020)
The chronicle backdrop of liver transplantation (LT) is an intricate story to reveal- it is an adventure of extraordinary achievement and catastrophic disappointments. Historically, controversies and LT seems to be synonymous.Despite the improvements in results, LT is still facing lots of challenges and controversies, whereby demand is high but the resources, primarily concerned to donor, are very limited. We have focused our perspective on LT for HCV-related cirrhosis and nutritional support for cachectic patients awaiting LT.